2020
DOI: 10.1097/tp.0000000000002955
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Early Sorafenib Treatment With mTOR Inhibitors in Hepatocellular Carcinoma Recurring After Liver Transplantation

Abstract: Background: Sorafenib (SOR) is currently used for hepatocellular carcinoma (HCC) recurring after liver transplantation (LT) when HCC is unsuitable for surgical/locoregional treatments. We evaluated safety and effectiveness of early introduction of SOR after HCC-recurrence. Methods: All patients with HCC-recurrence after LT treated with SOR in 2 centers were included (01/2008-06/2018). Baseline and on-treatment data were collected. Results: Fifty patients early treated with SOR for HCC-recurrence after LT (74% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…GEMOX showed complete response in fibrolamellar HCC. Combination therapy such as use of Sorafenib and mammalian target of rapamycin inhibitors[ 115 ] has been attempted with one year survival of 82% and five year survival of 33%[ 116 ]. New immunotherapy protocols such as atezolizumab-bevacizumab combination has not been studied in NCHCC, however future trials can be expected with these agents in NCHCC[ 117 ].…”
Section: Treatmentmentioning
confidence: 99%
“…GEMOX showed complete response in fibrolamellar HCC. Combination therapy such as use of Sorafenib and mammalian target of rapamycin inhibitors[ 115 ] has been attempted with one year survival of 82% and five year survival of 33%[ 116 ]. New immunotherapy protocols such as atezolizumab-bevacizumab combination has not been studied in NCHCC, however future trials can be expected with these agents in NCHCC[ 117 ].…”
Section: Treatmentmentioning
confidence: 99%
“…An earlier diagnosis of recurrence could help improve outcomes as several case series have shown improved survival in patients who underwent resection for localized recurrence compared to patients with multifocal recurrence . Early use of sorafenib and other mTOR inhibitors may also be options as well as resection or LRT, though more data are needed . In a metaanalysis of 1021 LT recipients with HCC recurrence, the median survival after diagnosis of recurrence was 13 months.…”
Section: Hcc Recurrence After Liver Transplantationmentioning
confidence: 99%
“…23,32,33 Early use of sorafenib and other mTOR inhibitors may also be options as well as resection or LRT, though more data are needed. 34 In a metaanalysis of 1021 LT recipients with HCC recurrence, the median survival after diagnosis of recurrence was 13 months. A variety of treatments were used including surgical resection, systemic therapy with sorafenib, LRT, and the best supportive care.…”
Section: Treatment Of Recurrent Hcc After Liver Transplantationmentioning
confidence: 99%
“…In the multivariable Cox proportional hazard analysis, the combination therapy (SOR plus EVL) was an independent predictive factor for better survival (RR: 0.320, 95% CI 0.014-0.660). Invernizzi et al reported similar results that the combination therapy (SOR plus EVL) is associated with better OS (MST: 18 months, 95% CI 8-27) after analyzing data of 37/50 patients treated with SOR in combination to EVL [25].…”
Section: Discussionmentioning
confidence: 78%
“…Theoretically, such systemic therapies could be a favorable approach and their combination (SOR plus mTORi) might have some synergetic effect for this systematic disease. However, there were few reports about the efficacy and safety of the combination therapy for recurrent HCC after LT [25][26][27]. The aim of this study was to evaluate the predictive factors of survival after HCC recurrence and to evaluate the efficacy and safety of the combination therapy (SOR plus EVL) as a treatment for HCC recurrence after LT.…”
Section: Introductionmentioning
confidence: 99%